Historical and Cultural Informativeness of French Phrasal Units with Component-dendronym (Proceedings of Southern Federal University. Philology, 2016)
Taisiya I. Skorobogatova, Olga Yu. Suraleva (Southern Federal University, Rostov-on-Don, Russian Federation)Research of national specificity of phraseology in a national language by distinguishing thematic groups of phraseological units and the analysis of their component composition becomes increasingly important in linguistic studies.This article is devoted to the analysis of the French phraseological units, which include dendronyms. Authors narrow notion of “dendronym” and use it only to refer to the names of trees.In French phraseological corpus authors identified 18 dendronyms, which are core components of the floral phrasal units: amandier (almond tree), cèdre (cedar), chêne (oak), cocotier (coconut palm), cyprès (cypress), figuier (fig tree), laurier (laurel tree), mûrier (mulberry), olivier (olive tree), orme (elm), osier (willow), palmier (palm), peuplier (poplar), platane (sycamore), poirier (pear), pommier (apple), prunier (plum), sapin (spruce, fir). The following list proves that the repertoire of dendronyms used to form French FU is not too wide. However, the authors confirmed the possibility to consider idioms-dendronym component as special items of historical and cultural memory.Key words: floral phraseology, phraseological unit, dendrons, historical/ cultural memory, the French language.DOI: 10.18522/1995-0640-2016-4-69-79